Single-cell RNA sequencing reveals adrb1 as a sympathetic nerve-regulated immune checkpoint driving T cell exhaustion and impacting immunotherapy in esophageal squamous cell carcinoma - Li, Qun; Xu, Shuning; Ren, Yulin; Zhang, Cheng; Li, Ke; Liu, Ying (Frontiers in Immunology, 2025)
BackgroundEsophageal squamous cell carcinoma (ESCC) presents significant health challenges due to its aggressive nature and poor prognosis from late-stage diagnosis. Despite these challenges, emerging therapies like immune checkpoint inhibitors offer hope. β1-adrenergic signaling has been implicated in T cell exhaustion, which weakens the immune response in ESCC. Blocking this pathway could restore T cell function. Recent advances in single-cell RNA sequencing (scRNA-seq) have enabled deeper insights into tumor heterogeneity and the immune landscape, opening the door for personalized treatment strategies that may improve survival and reduce resistance to therapy.MethodsWe combined scRNA-seq with bulk RNA analysis to explore adrenergic receptor signaling in ESCC, focusing on changes before and after neoadjuvant therapy. We identified ADRB1+ T cells through data analysis and experimental validation. Copy number variation (CNV) analysis detected malignant cells within scRNA-seq data, while intercellular interaction analysis examined communication between cell populations. Deconvolution of TCGA data revealed key immune populations, which were integrated into a prognostic model based on the adrenergic receptor signaling pathway and differentially expressed genes.ResultsThe adrenergic receptor signaling pathway was found in various immune cells, including T cells. scRNA-seq analysis revealed increased ADRB1 expression in T cells after neoadjuvant therapy. Immunofluorescence confirmed colocalization of ADRB1 with T cells, and fluorescence-activated cell sorting (FACS) showed that ADRB1 expression was elevated alongside exhaustion markers, while immune function markers were reduced. CNV analysis highlighted malignant cells in the tumor microenvironment, and intercellular interaction analysis explored ADRB1+ T cells’ role in immune support. Deconvolution of TCGA data identified ADRB1+ T cells, SPP1+ macrophages, and CD44+ malignant cells, all of which were prognostically significant. A prognostic model constructed from the intersection of the adrenergic receptor signaling pathway and differentially expressed genes following neoadjuvant therapy showed a significant prognostic effect.ConclusionsADRB1 expression increases after neoadjuvant therapy in ESCC and correlates with poor prognosis. Our findings suggest ADRB1 as a potential prognostic biomarker and therapeutic target for post-neoadjuvant immunotherapy.